Response of non-vascular epiphytes to simulated climate change in a montane moist evergreen broad-leaved forest in southwest China - Song, L.; Liu, Wen-Yao; Nadkarni, N. (Elsevier, 2012)
Interest in the potential effects of global climate change on forest ecosystems is increasing, but little is known about their effects on canopy communities, even though their reliance on atmospheric moisture and nutrients suggest that they are sensitive to current predictions of climatic change. We conducted a field experiment to assess the potential impacts of predicted climate change on the growth and health of four common non-vascular epiphytes at three elevations in a subtropical montane moist evergreen broad-leaved forest in southwest China. Even slight changes in climate resulted in remarkably reduced rates of growth and detrimental effects on the health of the transplanted epiphyte species over 2 years. Non-vascular epiphytes in this forest type respond much more rapidly to changes in water availability than terrestrial trees. The non-vascular lichen, Nephromopsis pallescens, is highly sensitive to changes in moisture and temperature, and could be adopted as a climate change indicator. Non-vascular epiphyte species may be negatively affected or even severely damaged in the future in subtropical montane forests, as climate conditions are predicted to be warmer and drier. This experiment confirms previous model projections and implies that conservation efforts to maintain the stability and resiliency of montane forest ecosystem to climate change should include epiphyte communities.